Penerapan Arsitektur Ekologi Pada Kawasan Agrowisata Tomohon Sulawesi Utara - Reinhard Jeremi Elkanatane; Tri Endangsih (MAESTRO, 2019)
Tomohon Agro Tourism in North Sulawesi is an architectural design with the ecological architecture application in its planning. The concept of architectural ecology is a constructive concept that pays attention to the balance of nature and artificial environment with humans, buildings and environment are the main elements. As an actors and users, human have a socio-cultural diversity to create buildings and environment harmonically. The design concept of architectural ecology is a plan that aims to design a system that is able to maintain the symbiosis of environment with buildings in order not to burden its natural cycle. On the other hand, the awareness of architecture student has begun to emerge to carry out its ecological insightful development processes. With the ecological nature that harmonizes an architectural concept with the surrounding environment, it provides conformity along the project. Agro-tourism areas that promote natural potential of flower plantations as a tourist attraction can be supported by an architectural touch. The diversity of types of flowers that exists in Tomohon city can create a specific space to discuss the object of the flower type. With this advantages, ecological concept can create a harmonization impression with flower plantation agro-tourism area in Tomohon, North Sulawesi.